CRITICAL ANALYSIS OF COMMUNICATION SYSTEMS IN EMERGENCY MEDICAL SERVICES: EVALUATING INTERAGENCY COORDINATION, INFORMATION SHARING, AND COMMUNICATION EFFECTIVENESS DURING EMERGENCIES - Abdullah Mohammad Ail Haqawi, Naif Saud Jubran Alshahrani, Badran Mosa Saleh, Amer Salem Hamad Al Sharyyan, Mohsen Shathan Almalki Yahya, Wuqayyan Mohammed Wuqayyan Alqahtani, Abdulmajeed Mushabbab Mohammed Alqahtani, Mohammed Hussain Mutiq Alqahtani,, (Chelonian Research Foundation, 2023)
One of the necessary aspects of the EMS system is capable coordination between different interagency agencies to ensure that information transfer and sharing will result in high-quality communication effectiveness during emergencies. This critical evaluation covers communications systems applied in EMS; it identifies their strengths, weaknesses, and conclusions about the effects of these communication systems on the results of the emergency service response. Through studying interagency coordination systems, information sharing criteria, and communication realization, this paper contributes a vision of how to improve the communication of EMS to help it become quicker and more effective. Keywords: emergency medical services, information communication systems, interagency cooperation, information sharing, communication efficiency.